2012
DOI: 10.1158/1940-6207.capr-12-0316
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Link Between Genome-Wide Hypomethylation in Blood and Cancer Risk?

Abstract: Cancer cells display widespread genetic and epigenetic abnormalities, but the contribution to disease risk, particularly in normal tissue before disease, is not yet established. Genome-wide hypomethylation occurs frequently in tumors and may facilitate chromosome instability, aberrant transcription and transposable elements reactivation. Several epidemiologic case-control studies have reported genomic hypomethylation in peripheral blood of cancer patients, suggesting a systemic effect of hypomethylation on dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 113 publications
(230 reference statements)
6
105
0
2
Order By: Relevance
“…[10][11][12][13] For example, if a particular blood cell subtype were associated with both LINE1%5mC level and bladder cancer risk, then the varying proportions could either confound or modify the association, resulting in different pre-and post-bladder cancermethylation associations. In bladder cancer, alterations have been observed primarily in the number of neutrophils, and in some cases, leukocytosis (increased leukocyte/white blood cell count) has been associated with poor prognosis, but not in the earliest stages of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[10][11][12][13] For example, if a particular blood cell subtype were associated with both LINE1%5mC level and bladder cancer risk, then the varying proportions could either confound or modify the association, resulting in different pre-and post-bladder cancermethylation associations. In bladder cancer, alterations have been observed primarily in the number of neutrophils, and in some cases, leukocytosis (increased leukocyte/white blood cell count) has been associated with poor prognosis, but not in the earliest stages of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…13 A second meta-analysis did not, with the exception of studies using a total 5mC assay. 12 Included in this meta-analysis were two retrospective studies, one of breast 18 and one of renal cancer, 19 that showed increased cancer risk among those with higher methylation levels using the luminometric methylation assay (LUMA) and LINE1 assays, respectively. Although the Xu et al, 18 study did not find associations with breast cancer risk using the LINE1 assay, the inconsistency was considered to be reflecting the different genomic areas examined by each assay: the LINE1 assay measures CpG sites throughout LINE1 sequences spanning the genome; the LUMA assay measures 5mC levels in the C m CGG motif, a sequence over-represented in gene promoter regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations